PD-L1 expression combined with microsatellite instability/CD8+ tumor infiltrating lymphocytes as a useful prognostic biomarker in gastric cancer - Morihiro, Toshiaki (Sci Rep, 2019)
While the importance of programmed death-ligand 1 (PD-L1), mutation burden caused by microsatellite instability (MSI), and CD8+ tumor infiltrating lymphocytes (TILs) has become evident, the significance of PD-L1 expression on prognosis still remains controversial. We evaluated the usefulness of combined markers of PD-L1 and MSI or CD8+ TILs as a prognostic biomarker in gastric cancer. A total of 283 patients with gastric cancer were reviewed retrospectively. PD-L1 expression on >5% tumor cells was defined as PD-L1-positive. PD-L1-positive rate was 15.5% (44/283). PD-L1 positivity was significantly correlated with invasive and advanced cancer and also significantly correlated with MSI, whereas no significance was observed with CD8+ TILs. Kaplan–Meier analysis showed that PD-L1 positivity significantly correlated with a poor prognosis (p = 0.0025). Multivariate analysis revealed that PD-L1 positivity was an independent poor prognostic factor (hazard ratio [HR]: 1.97, p = 0.0106) along with diffuse histological type and lymph node metastases. Combinations of PD-L1 and MSI (HR: 2.18) or CD8+ TILs (HR: 2.57) were stronger predictive factors for prognosis than PD-L1 alone. In conclusion, combined markers of PD-L1 and MSI or CD8+ TILs may be more useful prognostic biomarkers in gastric cancer, and better clarify the immune status of gastric cancer patients.